Analisis Kawasan Pariwisata Bahari Di Kabupaten Minahasa Tenggara - Falentino Mokolensang; Sonny Tilaar; Raymond Tarore (Sabua : Jurnal Lingkungan Binaan dan Arsitektur, 2021)
Southeast Minahasa has growing tourism potential, however, several tourism objects need attention, such as the marine tourism area. Cooperation between the government, the private sector and the community is urgently needed. The purpose of this research is to identify the potential of marine tourism areas in Southeast Minahasa Regency, to map the zoning of marine tourism areas in Southeast Minahasa Regency. The research was conducted using secondary data analysis methods obtained in several related institutions and equipped with survey methods then assisted by field observations, data analysis including potential objects was carried out by observation and identification. Potential objects are obtained from the tourism object assessment criteria and the assessed assessment technique, then the total score found is classified as applying the interval class method in the low, medium and high categories. The results showed that Lakban Beach was included in a high combined potential. Lumintang Beach, Bentenan Beach, Punten Island and Naga Island (Dakokayu) belong to the mixed potential class. Meanwhile, Baling-Baling Island, Hais Beach and Pasir Panjang Beach are included in the low combined potential class. There are three marine tourism zones, namely the coastal zone, the sea level zone, the underwater zone, the distributionzone for the location of marine tourism areas which are implemented in the form of a Geographical Information System in the form of a thematic map. Keywords: Potential, Maritime Tourism, Zoning.